The Call to Selfhood: Kierkegaard, Narrative Unity, and the Achievement of Personal Identity - Farris, Jacob (Kierkegaard studies / Yearbook, 2023)
This paper argues for a Kierkegaardian account of personal identity in dialogue with MacIntyre, Korsgaard, Frankfurt, Ricœur, and Marion. I engage with the scholarly debate on Kierkegaard's relationship to practical and narrative accounts of the self and argue that he criticizes the ideal of self-authorship because authentic selfhood must be co-authored with others and embedded in the narrative setting and history that is provided by facticity. Moreover, this relation to facticity requires ethical commitment and existential faith. The phenomenology of the call can show how such commitment and faith overcomes self-alienation by synthesizing the passive and active aspects of selfhood.